PENGARUH DRAMA KOREA TERHADAP DRAMA PADA PERTELEVISIAN INDONESIA (Study Kasus Drama My Love From The Stars dan Kau yang Berasal dari Bintang) - Sintowoko, Dyah Ayu Wiwid (Capture : Jurnal Seni Media Rekam, 2015)
This research tried to know the influence of Korean drama entitled My LoveFrom The Stars toward Indonesian drama Kau yang Berasal dari Bintang. This research constituted as qualitative descriptive research with those two dramas as the objects. The findings showed that the Indonesian drama Kau yang Berasal dari Bintang drama has similarity with the Korean drama My Love From The Star in the storyline, setting, and costumes. In the storyline, both dramas used a historical time describing love story between alien and human. In the costumes, Kau yang Berasal dari Bintang, used traditional costumes like Kebaya (to show the setting time in 400 years ago) and in the My LoveFrom The Stars used Hanbok as a traditional costumes too. The similarities in the setting are both of them used outdoor area (to describe pre-modernism) and crowded city (to describe modernization area).Keywords : Korean drama, storyline, costume, dan setting.